Urinary cytology and quantitative BTA and UBC tests in surveillance of patients with pTapT1 bladder urothelial carcinoma - Babjuk, Marko; Soukup, Viktor; Pešl, Michal; Koštířová, Milada; Drncová, Eva; Smolová, Helena; Szakácsová, Monika; Getzenberg, R; Pavlík, Ivan; Dvořáček, Jan (Urology, 2008)
OBJECTIVES: To compare results of urinary cytology, quantitative detection of human complement factor H-related protein (BTA TRAK), and urinary fragments of cytokeratins 8 and 18 (UBC IRMA) with the recurrence status in patients with pTapT1 bladder cancer and to define the possible role of these methods in a surveillance protocol.
Keywords: dospělí; nádorové biomarkery; senioři nad 80 let; invazivní růst nádoru; Neoplasm Invasiveness; Biomarkers, Tumor; Predictive Value of Tests; Humans; surveillance populace; urotel; lidé středního věku; lokální recidiva nádoru; nádory močového měchýře; Antigens, Neoplasm; Aged, 80 and over; Cohort Studies; Middle Aged; Financing, Organized; financování organizované; mužské pohlaví; Neoplasm Recurrence, Local; Adult; Urinary Bladder Neoplasms; karcinom; antigeny nádorové; Population Surveillance; ženské pohlaví; lidé; Urothelium; kohortové studie; Aged; Carcinoma; prediktivní hodnota testů; senioři; Male; Female